A computer vision system for automatic knowledge-based configuration of the image processing and hierarchical object recognition - Vu, A.S. (International Conference on Image Analysis and Processing: Proceedings; September 27-29, 1999, Venice, Italy, 1999)
In this paper a computer vision system is described which configures automatically programs for image processing and supports the recognition of objects. The system runs in two phases. In the first phase based on the primitives (curved edges, corners etc.) and the explicit specification of the content of the image given by the user a sequence of operators will be generated and all their free parameters will be computed adaptively. In this phase the system uses a rule base composed of knowledge of visual processing operators, their parameters, and their interdependence. In the second phase a hierarchical object model is formulated and edited by the user based on the primitives selected in the first phase. The system editor is specially provided for this purpose. Using the hierarchical object model facilitates a rapid interpretation of the result obtained from the previous image processing for the subsequent object recognition.